School Literacy Movement Educational Program in Shaping the Reading Character of Elementary School Students: Using the CIPP Model - Cahyani, Anita; Slamet, Sty; Sudiyanto, Sudiyanto (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the effectiveness of the School Literacy Movement (GLS) in fostering a reading habit among elementary students using the CIPP evaluation model. Methodology: The study used a qualitative case study design. Data were collected through structured interviews, direct observations, and document analysis. The CIPP model (Context, Input, Process, Product) was used as the evaluation framework. Triangulation and Miles & Huberman's interactive model were applied for data validation and analysis. Main Findings: Schools with strong leadership, teacher involvement, and community support were more effective in implementing GLS. Activities such as daily reading routines, reflective journals, and integrated literacy learning contributed to students' enthusiasm and consistent reading habits. Schools with weak support structures lacked systemized literacy outcomes. Novelty/Originality of this study: of this Study: This study offers a comprehensive evaluation of GLS using the full CIPP framework, integrating contextual and systemic factors rarely examined in previous studies. It provides evidence-based insights on how program alignment influences sustainable literacy character development in elementary education.